2022
DOI: 10.1177/19389655221102385
|View full text |Cite
|
Sign up to set email alerts
|

Do Brand-Affiliated Hotels Have Lower Cash-Flow Risk?

Abstract: Hotels are generally perceived as the riskiest type of commercial real estate (CRE) investment because hotel “leases” have relatively high turnover. Existing literature regarding CRE investment risk and return lacks investigation of hotels at the unit level—which is the level of analysis undertaken by existing and prospective hotel investors. Two major types of hotels are branded and independent ones. The purpose of this study is to investigate the variability (risk) of key performance indicators (KPIs) such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…First, hotel brand affiliation status, that is, chain-branded, soft-branded, and independent; appeared to substantially affect hotel operating profit variability (risk) during the period of 2015 through 2020 (which included the recession of 2020), with branded hotels displaying less profit variability than soft-branded and independent hotels. This finding appears to be consistent with prior research which demonstrated that while branded and independent hotels recorded comparable profitability during economic growth cycles, branded hotels outperformed nonbranded ones during economic recessions (Liu & O’Neill, 2023; O’Neill & Carlback, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…First, hotel brand affiliation status, that is, chain-branded, soft-branded, and independent; appeared to substantially affect hotel operating profit variability (risk) during the period of 2015 through 2020 (which included the recession of 2020), with branded hotels displaying less profit variability than soft-branded and independent hotels. This finding appears to be consistent with prior research which demonstrated that while branded and independent hotels recorded comparable profitability during economic growth cycles, branded hotels outperformed nonbranded ones during economic recessions (Liu & O’Neill, 2023; O’Neill & Carlback, 2011).…”
Section: Discussionsupporting
confidence: 91%